p(x) = 2x + 1
⇒ p(-1/2) = 2(-1/2) + 1
⇒ p(-1/2) = -1 + 1
⇒ p(-1/2) = 0
∴ Yes x = -1/2 is the zero of polynomial 2x + 1.
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
Write whether theAP- Mathematics
Classify the follAP- Mathematics